Effectiveness of the right of access to health of people in street situations front of the COVID-19 pandemic (Research, Society and Development, 2022)
The present study sought to evaluate, based on the specialized literature, how the right of access to health by homeless people has been affected in the face of the COVID-19 pandemic. This is an integrative review research carried out through an advanced search in the SciELO, PubMed, Science Direct, BVS and LILACS databases, with selection of articles made with the following Health Sciences Descriptors (DeCS): “People on the Street”, “Right to Health”, “Access to Health Services” and “COVID-19”, and their respective terms translated into English. Among the documents and articles found, 16 were selected because they fit the purpose of the study. The barriers imposed by the COVID-19 pandemic on homeless populations are notorious, especially when the right of access to health is verified by this social group. Specifically in its most acute phase, the pandemic was and still has been marked by insufficiency in hygiene and social isolation measures for this segment. In addition, health vulnerability is observed in higher mortality rates among homeless people compared to the general population, as well as the fragmentation of mental health care aggravated by the pandemic. Strategies were taken to protect and provide health care to the homeless population. However, an insufficiency in the implementation of such strategies by states and municipalities is observed, demonstrating the need for effective health care to guarantee the rights of this population.